A atividade sinfônica em Belo horizonte entre: esperanças e lutas - Gustavo Anibal Napoli Villalba (2016)
This study aims to analyze historically the origins and consolidation of symphonic activity in Belo Horizonte and its consequences in terms of management. In fact, we intend to see that, with the modern view that is denoted with the creation of new capital and the advent of an auspicious time, the incorporation of symphonic activity to the mining culture was a model understood by Brazilian intellectuals as synonymous of sophistication and progress, consistent with the improvement of culture in the state. It will be noted especially the degree of prestige attributed to the Symphony Orchestra of Minas Gerais and their recognition as cultural heritage and "stable artistic body of the Palace of Arts, larger home state of Minas Gerais shows. We will see how the concept of modernity applied by public policies for culture was being modified in accordance with the trends and political will.